2016
DOI: 10.1590/1519-6984.08115
|View full text |Cite
|
Sign up to set email alerts
|

Storage of Calophyllum brasiliense Cambess. seeds

Abstract: Calophyllum brasiliense is a species native to Brazil and has potential for use in the timber industry, in the reforestation of degraded areas, besides having medicinal properties. Its propagation is mainly by seeds which, depending on their recalcitrant characteristics, leads to difficulty in conservation, due to changes in its physiological potential during storage. Aiming to contribute to the expansion of its cultivation, rational use and conservation, the objective of this study was to investigate the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…As for guanandi seed storage, generally speaking, in all the tested environments the polyethylene packaging was the one that best preserved the physiological potential of seeds throughout the storage period ( Figure 2). Nery et al (2017) also observed that the use of polyethylene packaging (resistant to water vapor exchanges) was the most suitable for preserving moisture content of guanandi seeds.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…As for guanandi seed storage, generally speaking, in all the tested environments the polyethylene packaging was the one that best preserved the physiological potential of seeds throughout the storage period ( Figure 2). Nery et al (2017) also observed that the use of polyethylene packaging (resistant to water vapor exchanges) was the most suitable for preserving moisture content of guanandi seeds.…”
Section: Discussionmentioning
confidence: 89%
“…Guanandi seeds, for being recalcitrant (NERY et al, 2017), do not tolerate intensive desiccation or the exposure to low temperature. In this study, it was observed that by maintaining a proper seed moisture content, the determining factor to maintain viability started to be the temperature, since when seeds were stored in polyethylene packaging, they presented no significant humidity reduction in three different environments; however, they maintained a higher quality during the entire storage period only under laboratory environment conditions, which presented in the period an average temperature variation between 19.6 and 23.1 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nery et al [40] tested different packages (paper, aluminum and polyethylene) and environmental conditions (cold room and ambient temperature) for the storage of Guanandi (Calophyllum brasiliense) and concluded that packaging in polyethylene and cold storage provided the best condition for the conservation of the seeds keeping them viable for a period of nine months.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of the techniques that seek to improve the quality of forest seed lots is to select homogeneous material with high physiological potential, thus ensuring the best growth and establishment of the plants in the field. Consequently, there will be greater acceptance in the market and in reforestation activities (Amaral et al, 2011;Nery et al, 2017). This study aimed to analyze the physical properties of the seeds of M. polymorphum when processed by mini-SAS, X-ray and seed blower systems.…”
Section: Introductionmentioning
confidence: 99%